Electrochemical Corrosion Behavior of High Strength Carbon Steel in H2S-Containing Alkaline Brines. (7th August 2015) - Feng, Ruishu; Beck, Justin; Buyuksagis, Aysel; Wolfe, Ian; Cianni, Rosemary; Ziomek-Moroz, Margaret; Lvov, Serguei N.
Abstract : The electrochemical corrosion behavior of high strength low alloy carbon steel API S-135 was investigated using in-situ electrochemical measurements, ex situ surface analyses, and software modeling in the alkaline brines at pH of 7.9, 10.7, and 12.4 and at four different P H2S equal to 0 kPa, 0.83 kPa, 8.3 kPa, and 69 kPa at 85 o C. Linear polarization resistance ( R pol ) at steady state increased as pH increased from 7.9 to 12.4 at lower P H2S whereas R pol decreased and then increased at higher P H2S . The fastest corrosion rate (CR) was 0.26 mm yr -1 at pH 10.7 with P H2S 69 kPa, and the slowest CR was 0.0053 mm yr -1 at pH 12.4 with P H2S 0.83 kPa. The correlation between the primary species, corrosion products, localized corrosion and R pol were discussed. The experimental CR and corrosion products were compared with the modeling CR and Pourbaix diagram.